Evaluasi User Experience Aplikasi Exstraordinary Computer Based Test pada Penilaian Mata Kuliah Pemrograman Materi HTML - Kurniawan, Edi; Nugraha, Markus Asta Patma; Kurniawan, M. (PAKAR Pendidikan, 2025)
This study aims to evaluate the use of the Extraordinary Computer-Based Test (CBT) application in assessing the HTML Programming course at the Politeknik Pelayaran Sumatera Barat. The method used is quantitative with a program evaluation design based on the CIPP model (Context, Input, Process, Product). The subjects of the study consisted of 62 third-semester students from the eighth batch of 2024, divided into three classes. Data were collected through learning achievement tests, questionnaires, and practical assessment rubrics, focusing on the cognitive, affective, and psychomotor domains. The results of the study indicate that the CBT application is effective in improving students' learning outcomes. The average score for the cognitive aspect reached 83, with the highest scores in the structure and development of HTML applications. The affective evaluation showed positive student responses to CBT, with an affective aspect score of 82, while the psychomotor evaluation showed adequate practical skills with a score of 80. This study reveals that CBT enhances the effectiveness of assessments and enriches students' learning experiences by providing real-time feedback and more personalized guidance. The findings contribute to the development of technology-based learning tools and offer practical solutions to improve the quality of education. Furthermore, this study concludes that CBT can improve the quality of evaluation and learning in HTML programming and recommends further development to integrate other technologies into the learning process.